Adequate Investment Portfolio Anatomy and Decisions Applying Imitative Technologies - Rutkauskas, Aleksandras Vytautas (Ekonomika, 2006)
The paper consistently analyses the process of the author’s so-called adequate investment portfolio formation; also, adequate portfolio application analogies with the modem or Markowitz portfolio are presented. Adequate portfolio application peculiarities are disclosed when investment assets possess complex probability distributions of profitability possibilities, as well as for the integrated management of assets and liabilities. Imitation modelling possibilities, of solving the model system expressing adequate portfolio contents are also examined. Such system generally appears to be a complex stochastical programming task, thus original methods of problem formulation and decision-making are required for its analysis. The paper describes situation representative analogue idea, the essence of which is expressed by the of an application integrated representative set and imitation modelling possibilities. Finally, the paper illustrates an adequate investment portfolio and situation representative analogue application for solving a particular of problem investment. For an adequate portfolio development and management, the imitation technologies technique presented by the author is used. It allows finding decisions for portfolio objectives expressed as stochastical programming tasks at a desired level of accuracy.